PENERAPAN PERLUASAN ARTI PERBUATAN MELANGGAR HUKUM DALAM PELAKSANAAN UU 29 TAHUN 2004 (STUDI KASUS PUTUSAN NO.625/PDT.G/2014/PN JKT. BRT) - Purwanto, Agus; Sunarsi, Denok; Wijoyo, Hadion (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The development of the health and disease management technology supporting advanced as well as facilities. The purpose of this research is to know the operation process had involved the cecum to the / appendicitis the act of an anesthetic of medical staff that cause financial losses for patients in the implementation of the Act Of Law number 29 years 2004 about the practice of medicine to gain an understanding of the factors causing the an appendectomy / appendicitis with the action of an anesthetic by of medical staff that cause financial losses for patients in the implementation of the Act Of Law number 29 years 2004 about the practice of medicine . As for the methodology used an author in the juridical research methodology is normative and for scholarly activities which includes the stock taking , explained, to interprate, Systemize , and evaluate all the positive law applicable in a community or state , Based on concepts, definitions , categories , theories , clasifications , and methods formed and developed specifically to do all the activities are , that whole to prepare their activities are hoping to find a settlement to the problem of juridical law that might happen dimasyarakat in this regard to judicial decisions No. 625/PDT.G/2014/PN JKT. BRT. The results of the study and discussion can be obtained the conclusion that the act of an anesthetic by medical workers and paramedics in running expertise their which have inflicted losses for patients can be accounted for because still have to keep / based on the guidelines regulations and policy staged it set out in the act of no. 29 / 2004 about the practice of medicine, the act of no. 36 2009 on health, policy and directions head of  MKDKI and KKI keputusan and regulations as well as the failure medical for every health worker / health workers in performing an action medical could be accounted for on all medical workers and paramedics who do it out of regulations and policies that exists because caused by other factors expansion of understanding unlawful act which includes not only flouted the rules written will but including also worried the rights of others, contrary to a legal obligation A maker of , contrary to morality and contrary to propriety , precision , and that should be taken in between hati-hatian community against the body or objects .Then required / regulations about the outcome of a policy governing ( resultaat verbintenis ) or in the business / ( inspaning verbintenis ) / medical workers health workers in performing medical procedures because / regulations about the outcome of a policy governing ( resultaat verbintenis ) business or power (inspaning verbintenis)